De relatie tussen verkleinwoorden en verkortingen : een vergelijking tussen drie West-Germaanse talen - Camiel Hamans (Brünner Beiträge zur Germanistik und Nordistik, 2016)
In this paper clipping in Dutch, English and German is discussed. In English there exist three different processes of clipping. The first results in monosyllabic CVC-forms, the two others in disyllabic trochaic forms, the first of this pair with final –o , the last one ending in –i. In Dutch there are mainly two processes of clipping. The first one resulting in monosyllabic CVC-forms, the second in trochaic forms ending in –o. German also has disyllabic clipped forms but mainly ending in –i. This paper shows how the co-occurrence of a diminutive or hypocoristic suffix –i in German and the absence of a similar suffix in Dutch can explain the non-occurrence of –i clipped forms in Dutch and at the same time of –o clipped forms in German.